An improved mouse model that rapidly develops fibrosis in non‐alcoholic steatohepatitis. Issue 2 (11th January 2013) - Matsumoto, Masahiko; Hada, Natsuko; Sakamaki, Yoshiyuki; Uno, Akiko; Shiga, Toshihiko; Tanaka, Chiaki; Ito, Tsuneo; Katsume, Asao; Sudoh, Masayuki
Summary Non‐alcoholic steatohepatitis (NASH) is a progressive fibrotic disease, the pathogenesis of which has not been fully elucidated. One of the most common models used in NASH research is a nutritional model where NASH is induced by feeding a diet deficient in both methionine and choline. However, the dietary methionine‐/choline‐deficient model in mice can cause severe weight loss and liver atrophy, which are not characteristics of NASH seen in human patients. Exclusive, long‐term feeding with a high‐fat diet (HFD) produced fatty liver and obesity in mice, but the HFD for several months did not affect fibrosis. We aimed to establish a mouse model of NASH with fibrosis by optimizing the methionine content in the HFD. Male mice were fed a choline‐deficient, L‐amino acid‐defined, high‐fat diet (CDAHFD) consisting of 60 kcal% fat and 0.1% methionine by weight. After 1–14 weeks of being fed CDAHFD, the mice were killed. C57BL/6J mice maintained or gained weight when fed CDAHFD, while A/J mice showed a steady decline in body weight (of up to 20% of initial weight). In both strains of mice, plasma levels of alanine aminotransferase increased from week 1, when hepatic steatosis was also observed. By week 6, C57BL/6J mice had developed enlarged fatty liver with fibrosis as assessed by Masson's trichrome staining and by hydroxyproline assay. Therefore, this improved CDAHFD model may be a mouse model of rapidly progressive liver fibrosis and be potentially useful for better understanding human NASH disease and in the development of efficient therapies for this condition.